ANALISIS FAKTOR YANG MEMPENGARUHI PRICE EARNING RATIO SEBAGAI DASAR PENILAIAN SAHAM - Weni Susanti; Mardhiyah Dwi Ilhami (Universitas Prof.Hazairin,SH Bengkulu, 2018)
The purpose of research is to test and analyze the factors influence Price EarningRatio as basic of stock appraisal on manufacture companies listed in Indonesia StockExchange of from 2009-2013. This research is descriptive research with quantitativeapproach. Method of collecting data uses documentation is secondary data weresourced from Capital Market Directory in 2009-2013and data were sourced fromIndonesia Stock Echange Company Report in year 2013. Method of data analysis usesFactor Analysis, especially EFA(Explanatory Factor Analysis) through method of PCA(Principal Component Analysis). Results of the research showed that (1) factor ofcapitals and debts with percentage35.297%, it means this factor is dominant factor canexplain 35.297%of the variables’ variance; (2) factor of dividends and shares withpercentage 30.293%, it means this factor can explain 30.293% of the variables’variance; (3) factor of benefits level with percentage 21.254%, it means this factor canexplain 21.254% of the variables’ variance; (4) factor of sales level with percentage6.747%, it means this factor can explain 6.392% of the variables’ varianceand (5) otherfactors with percentage 6.747%, it means this factor can explain 6.392%of thevariables’ variance.